Applying the Social Development Model in Middle Childhood to Promote Healthy Development: Effects from Primary School Through the 30s and Across Generations - Catalano, Richard F. (Journal of developmental and life-course criminology, 2021)
This paper describes the origins and application of a theory, the social development model (SDM), that seeks to explain causal processes that lead to the development of prosocial and problem behaviors. The SDM was used to guide the development of a multicomponent intervention in middle childhood called Raising Healthy Children (RHC) that seeks to promote prosocial development and prevent problem behaviors. This paper reviews and integrates the tests of the SDM and the impact of RHC. While the original results of both model and intervention tests have been published elsewhere, this paper provides a comprehensive review of these tests. As such, this integrative paper provides one of the few examples of the power of theory-driven developmental preventive intervention to understand impact across generations and the power of embedding controlled tests of preventive intervention within longitudinal studies to understand causal mechanisms., Application of the SDM in the RHC intervention was tested in a quasi-experimental trial nested in the Seattle Social Development Project (SSDP). SSDP is a longitudinal study of 808 students who attended 18 public schools in Seattle, WA, and whose parents consented for their participation in longitudinal research when they were in grade 5 (77% of the eligible population in participating schools). Students assented at each survey administration and consented to longitudinal follow-up when they turned 18. Panel subjects were followed and surveyed 15 times from grade 5 through age 39, with most completion rates above 90%., We describe effects of the full multicomponent RHC intervention delivered in grades 1 through 6 by comparing outcomes of those children assigned to the full RHC intervention condition to controls from middle childhood through age 39. We also report the effects of the full RHC intervention on the firstborn children of participants compared with the firstborn children of controls., We discuss the use of the theory to guide the development and testing of preventive interventions and the utility of nesting intervention tests within longitudinal studies for testing both theory and interventions.